Implementing an ecosystem approach in public administration: achieving sustainable development goals in crisis and recovery - Berezovska, Nina; Zahorskyi, Volodymyr; Kalashnyk, Nadiia; Novak-Kalyayeva, Larysa; Lipentsev, Andriy; Olefirenko, Olha; Oliyarnyk, Volodymyr; Sushynskyi, Oleksandr (Cadernos de Educação Tecnologia e Sociedade, 2024)
The article explores the potential of the ecosystem approach in transforming public administration to meet pressing demands. It examines how the ecosystem framework can guide decision-making and resource management in ways that promote resilience, inclusivity, and sustainability. The research highlights the critical intersections of governance, environmental protection, and socio-economic development, offering a roadmap for aligning Ukraine’s reconstruction efforts with global sustainability benchmarks. The study begins by addressing the theoretical foundations of the ecosystem approach and its relevance to public administration. It then investigates practical applications, focusing on indicators and methodologies for achieving SDGs within the context of Ukraine’s recovery and ongoing European integration. Finally, it proposes strategies for fostering multi-level governance, stakeholder participation, and adaptive policymaking in a rapidly changing and uncertain environment. By addressing these themes, this article contributes to the discourse on innovative governance practices, providing insights into how an ecosystem approach can reshape public administration to navigate the dual imperatives of crisis response and sustainable development. The authors provide a reasoned classification of key challenges in implementing the ecosystem approach in modern public administration. Based on the challenges, research areas of ecosystem approach in public administration are proposed, and the main research questions of these areas are given. The needs for research in the indicated areas are proven through their correlation with SDGs. The authors propose key indicators for achieving the SDGs in the reconstruction of Ukraine based on the principles of the Ukraine Facility 2024-2027 plan.